Patient experience of treatment decision making for wet age-related macular degeneration disease: a qualitative study in China. Issue 9 (3rd September 2019) - Bian, Wei; Wan, Junli; Tan, Mingqiong; Wu, Xiaoqing; Su, Jun; Wang, Lihua
Abstract : Objectives: This study aimed to investigate the experience of patients with wet age-related macular degeneration (wAMD) in treatment decision-making process. Design: A descriptive qualitative study was designed by using semistructured interviews, and the data analysis was conducted with the thematic analysis approach. Participants and setting: A convenient and purposive sample of 21 participants diagnosed with wAMD was recruited from May 2018 to September 2018. The study was conducted in the Eye Clinic of Southwest Hospital of Army Medical University in Chongqing located in the southwest of China. Results: The mean age of the participants was 64.48 years (ranging 50–81 years), and the duration of the disease ranged from 6 months to 48 months. Four major themes were identified from the original data analysis. These themes included facing the darkness (choosing from light and darkness and living in pain), constraints on decision making (doctor-oriented decision making, inadequacy of options and time), weighing alternatives (family influence, financial burden and maintaining social function) and decision-making support (professional decision-making assistance and peer support). Conclusion: This is a qualitative study attempting to explore the patient experience of treatment decision making for wAMD disease in China. Previous literature has focused on treatment effect and symptoms, rather than the individual experience and the wide contexts from a sociocultural perspective. Further studies, such as cross-sectional studies, can be used to describe the status and determine the influencing factors of decision0making process, so as to develop an impact factor model of decision making and to formulate an intervention for patients with wAMD.